ANALISIS STRATEGI EFEKTIF DALAM MENJAGA KELESTARIAN BAHASA INDONESIA DI ERA DIGITAL: TANTANGA DAN PELUANG GENERASI MUDA - Devi Fifi Tarigan; Widia Abisah Br Ginting; Katrina Olivia; Sri Rahayu Rambe; Lili Tansliova (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
Indonesian plays a very large role in strengthening national identity, maintaining social unity, and facilitating communication between citizens, in an increasingly developing era, especially in this digital era, Indonesian faces various new challenges, one of which is the dominance of foreign languages, especially English, which is increasingly used in digital communication. This study aims to analyze effective strategies in maintaining the sustainability of Indonesian in the digital era by understanding the challenges and utilizing the opportunities available to the younger generation. This research method is a case study, or literature study. The results of the study show that Indonesian is a national identity that has an important role as a means of communication, unification, and cultural expression. However, in this digital era, Indonesian faces major challenges, such as the widespread use of foreign languages, simplification of language that is not in accordance with the rules, and the low interest of the younger generation in learning and using good and correct language.